2011
DOI: 10.1007/s11096-011-9510-5
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the role of trust in medication management within mental health services

Abstract: Safe management of medication is facilitated by trust. However, this trust may be difficult to develop and maintain, exposing service users to adverse events and worsening adherence. Practice and policy should be oriented towards developing trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…This echoes other research, which has found that service users with SMI value the opportunity to collaborate with those providing their care and are prepared to engage with SDM within the current patient-professional relationship [ 47 ]. SDM can also improve treatment knowledge amongst service users with schizophrenia potentially reducing the risk of medication errors [ 18 , 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This echoes other research, which has found that service users with SMI value the opportunity to collaborate with those providing their care and are prepared to engage with SDM within the current patient-professional relationship [ 47 ]. SDM can also improve treatment knowledge amongst service users with schizophrenia potentially reducing the risk of medication errors [ 18 , 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Department of Health White Paper stated that ‘care should be personalised to reflect peoples’ needs, not those of the professional or the system’ and patients should be involved in treatment decisions [ 17 ]. People diagnosed with SMI can be fully engaged with making decisions and seek a more collaborative approach, thus treatment decisions should be made by the service user and the healthcare professional working together and considering both the likely benefits and possible adverse effects of the medication [ 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The one who was adamant about him coming off the lorazepam had this one mind set. Trust develops over time, from seeing the same practitioner in whom they are confident, underscoring the importance of continuity of care to practice and practitioner relationships: [153][154][155][156][157] The patient-provider relationship is the fundamental starting point for patient centred care delivery. Central to the patient-provider relationship is trust.…”
Section: Box 28 Conflicting Information Provided By Practitioners To mentioning
confidence: 99%
“…These enable the ‘treatment’ of psychotic symptoms and are the cornerstone of modern medical approaches to dealing with severe mental illness and risk attributed to it. Clearly the effectiveness of these ‘risk management tools’ depends upon the extent to which prescribed medication is co‐operated with by the service‐user, yet once again the orientation of services towards control may tend towards undermining concordance: where ‘a perceived threat to an individual's freedom generates a motivational state aimed at recapturing the affected freedom and preventing the loss of others’ and where a corresponding non‐concordance results (Fogarty 1997: 1277; Maidment et al . 2011).…”
Section: Problems Inherent To Managing Risk: the Limitations And Undementioning
confidence: 99%